Designing Marketing Strategies of Mamaberry Chips Gourmet Using Swot Method and Quantitative Strategic Planning Matrix (QSPM) - Muhammad Ghafari Nurfathoni; Sari Wulandari; Ima Normalia Kusmayanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Based on Fortune Business Insight (2020) changes in healthy lifestyles by consuming organic food products are increasing becoming a global trend. Current consumer awareness of organic labels in the food sector continues to experience high market demand. This can be seen from the data that global sales of organic food reached $50.1 billion up 4.6% with a growth rate of 2% every year. The results of the 2020 survey were conducted by observing organic sales and the results show that consumers are increasing looking for organic labels, especially in the food sector. One of the effects is because consumers' perception of clean and healthy food is the main goal. Mamaberry Chips Gourmet is an MSME engaged in the healthy snack food sector. Mamaberry Chips Gourmet was founded in 2017 with a business-to-consumer (B2C) business model, which is a business model that focuses on marketing and selling products to consumers. Currently the company does not have a marketing strategy to face competition in the healthy snack business. Therefore, this final project aims to formulate a reliable strategy based on the company's resources to maximize existing opportunities. This final project uses the SWOT method and the IE Matrix to generate alternative strategies and the QSPM matrix to prioritize alternative strategies. Analysis using SWOT and IE Matrix resulted in a total of 12 strategies that could be implemented. Based on the evaluation conducted through QSPM, the strategy that needs to be prioritized by Mamaberry Chips Gourmet is the strategy of utilization and improvement of marketing channels with a total attractiveness score (TAS) of 6.52. The timing of the strategy implementation is then compiled through a roadmap of the strategy implementation plan each year.